Curcumin attenuates cytoplasmic/endoplasmic reticulum stress, apoptosis and cholinergic dysfunction in diabetic rat hippocampus - Keshk, Walaa A.; Elseady, Walaa S.; Sarhan, Naglaa I.; Zineldeen, Doaa H. (Metabolic brain disease, 2020)
Diabetes mellitus (DM) is associated with the increased risk of the central nervous system complications as cerebrovascular disease, impaired cognition, dementia and neurodegeneration. Curcumin is a polyphenol with anti-oxidant, anti-inflammatory, anti-hyperlipidemic, and anti-cancer effects. Therefore, the present study was aimed to focus on the mechanistic insights of diabetes-induced hippocampal neurodegeneration in addition to shedding the light on the modulatory effect of curcumin. Twenty-eight male Wistar rats were randomly divided into four groups. Type I DM was induced by a single intra-peritoneal injection of streptozotocin (STZ) (65 mg/kg b.w.). Curcumin (100 mg/kg b.w.) was given to the diabetic group after the induction and for eight weeks. Hippocampal glucose-regulated protein 78 (GRP78), activating transcription factor 4 (ATF-4), Bcl2 and choline acetyl transferase (ChAT) genes expression were assessed. Heat shock protein 70 (HSP70), Bcl-2-Associated X protein (Bax), Interferon-γ (INF-γ) and CCAAT-enhancer-binding protein homologous protein (CHOP) levels in the hippocampus were immunoassayed, in addition to the assessment of glycemic and redox status. Curcumin significantly improved blood glucose level, redox status, cellular stress, and decreased INF-γ and Bax levels, down-regulated GRP78 and ATF-4 expression, meanwhile, up-regulated Bcl2 and ChAT expression in hippocampus. Histological findings proved the biochemical and molecular findings. Our results support curcumin as a potential neuro-protective agent against diabetes induced hippocampal neurodegeneration.